1996
DOI: 10.1128/aac.40.11.2598
|View full text |Cite
|
Sign up to set email alerts
|

Effects of topical erythromycin on ecology of aerobic cutaneous bacterial flora

Abstract: We have demonstrated previously that application of topical erythromycin, an antibiotic commonly used for the treatment of acne, results in an increased density of cutaneous erythromycin-resistant (Emr) coagulase-negative staphylococci; however, it is unknown if this increase results in an overall higher density of total cutaneous staphylococci or if upon cessation of erythromycin use, Emr coagulase-negative staphylococci remain at an increased density compared with the pretreatment density. To investigate thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 20 publications
1
10
0
4
Order By: Relevance
“…This finding did not reach statistical significance. Similar effects on nasal S. aureus had been seen in prior studies (21).…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…This finding did not reach statistical significance. Similar effects on nasal S. aureus had been seen in prior studies (21).…”
Section: Introductionsupporting
confidence: 79%
“…The first possible explanation involves the direct transfer of antibiotics and/or bacterial organisms to the oropharynx via a person's fingers or by devices such as eating utensils. This theory is supported by the findings of several studies, which demonstrated an increase in erythromycin-resistant coagulase-negative staphylococci at sites (back and anterior nares) where antibiotic was not directly applied (21,31). An alternative less likely (blood levels so low) mechanism is systemic absorption of topically applied antibiotic, leading to hematogenous spread of drug to noncutaneous sites such as the oropharynx.…”
Section: Group a Streptococcusmentioning
confidence: 77%
“…In fact, changes in cutaneous flora have been reported with both topical and oral antibiotic use (6,(17)(18)(19)(20)(21)(22)(23). In fact, changes in cutaneous flora have been reported with both topical and oral antibiotic use (6,(17)(18)(19)(20)(21)(22)(23).…”
Section: Topical Antibiotic Use In Acne and Changes In Cutaneous Floramentioning
confidence: 99%
“…Potential issues of concern that have been raised in the literature include increased prevalence of P. acnes strains less responsive to antibiotics, alterations in cutaneous flora, decreased therapeutic responsiveness to antibiotic therapy, and promotion of other clinical infections among treated patients and/or their close contacts (6,17,18,(21)(22)(23)(24)26,27). Potential issues of concern that have been raised in the literature include increased prevalence of P. acnes strains less responsive to antibiotics, alterations in cutaneous flora, decreased therapeutic responsiveness to antibiotic therapy, and promotion of other clinical infections among treated patients and/or their close contacts (6,17,18,(21)(22)(23)(24)26,27).…”
Section: Comparison Of Topical Antibiotics In the Treatment Of Acnementioning
confidence: 99%
“…Both systemic and topical antibiotics are capable of changing the antibiotic-resistance patterns in bacteria. Topical erythromycin has been shown to produce overgrowth of antibiotic resistance bacteria both locally and at distant sites [10, 11]. Similar resistance trends are also likely to result from topical clindamycin monotherapy.…”
Section: Introductionmentioning
confidence: 99%